Fundamentalist ; Smoke belching ; Willem Dafoe [videorecording] - Laaro, Cheche (THe Probe Team, 1989)
Deals with the feud between Catholic church and the Bible Christians or Fundamentalists ; discusses the perrenial problems of smoke belchers in the metropolis ; and the interview with Hollywood actor, Willem Dafoe.